Evaluation of anti‑diabetic activity of AHPL/AYTAB/0513 tablet in streptozotocin induced diabetes in rats - Nipanikar, Sanjay U; Chitlange, Soham S; Nagore, Dheeraj (International Journal of Pharmaceutical Investigation)
Background: Diabetes is a chronic, progressive disease associated with several complications leading to significant mortality and morbidity. Limitations and drawbacks of the conventional treatment generate need for safer, effective complimentary therapies to prevent complications, and maintain normoglycemic status. Aim and Objectives: The aim of this study is to to evaluate antidiabetic activity of AHPL/AYTAB/0513 tablet alone, oral hypoglycemic agents (OHA[s]), and combination of AHPL/AYTAB/0513 tablet and OHA(s) in streptozotocin‑induced diabetes in rats. Materials and Methods: Totally, ten groups of animals were studied comparatively to evaluate antidiabetic activity of AHPL/AYTAB/0513 tablet, OHA(s), and combination of AHPL/AYTAB/0513 tablet and OHA(s). Blood glucose level (BGL), lipid profile, serum creatinine, serum insulin level, and histopathological characteristics of pancreas were studied to evaluate the efficacy of various formulations. Histopathological examination of kidney and heart was carried out to assess the ability of various formulations in preventing complications of diabetes. Results: There was a significant decrease in mean BGL, serum triglycerides, serum total cholesterol, low‑density lipoprotein (LDL), very LDL, and serum creatinine levels in all formulations groups. Significant increase in mean serum insulin level and high‑density lipoprotein level was observed when compared to diabetic control (DC) group. Recovery of pancreatic beta cells and prevention of damage to heart and kidney cells was significant in all the formulation groups as compared to DC group. None of the formulations tested in nondiabetic rat showed hypoglycemia suggesting safety of all the formulations. Conclusion: AHPL/AYTAB/0513 tablet alone and in combination with OHA(s) can be effectively used in the management of diabetes mellitus. In addition, AHPL/AYTAB/0513 tablet alone and in combination with OHA(s) help in prevention of diabetic complications. As an adjuvant to OHA(s), AHPL/AYTAB/0513 tablet can be more effective.
Keywords: Adjuvant to oral hypoglycemic agent; AHPL/AYTAB/0513 tablet; antidiabetic; diabetic complications; polyherbal; Type II Diabetes